Type and case volume of health care facility influences survival and surgery selection in cases with early‐stage non–small cell lung cancer. Issue 23 (10th September 2019) - Wang, Shidan; Lai, Sunny; von Itzstein, Mitchell S.; Yang, Lin; Yang, Donghan M.; Zhan, Xiaowei; Xiao, Guanghua; Halm, Ethan A.; Gerber, David E.; Xie, Yang
Abstract : Background: With the expansion of non–small cell lung cancer (NSCLC) screening methods, the percentage of cases with early‐stage NSCLC is anticipated to increase. Yet it remains unclear how the type and case volume of the health care facility at which treatment occurs may affect surgery selection and overall survival for cases with early‐stage NSCLC. Methods: A total of 332, 175 cases with the American Joint Committee on Cancer (AJCC) TNM stage I and stage II NSCLC who were reported to the National Cancer Data Base (NCDB) by 1302 facilities were studied. Facility type was characterized in the NCDB as community cancer program (CCP), comprehensive community cancer program (CCCP), academic/research program (ARP), or integrated network cancer program (INCP). Each facility type was dichotomized further into high‐volume or low‐volume groups based on the case volume. Multivariate Cox proportional hazard models, the logistic regression model, and propensity score matching were used to evaluate differences in survival and surgery selection among facilities according to type and volume. Results: Cases from ARPs were found to have the longest survival (median, 16.4 months) and highest surgery rate (74.8%), whereas those from CCPs had the shortest survival (median, 9.7 months) and the lowest surgery rate (60.8%). The difference persisted when adjusted by potential confounders. For cases treated at CCPs, CCCPs, and ARPs, high‐volume facilities had better survival outcomes than low‐volume facilities. In facilities with better survival outcomes, surgery was performed for a greater percentage of cases compared with facilities with worse outcomes. Conclusions: For cases with early‐stage NSCLC, both facility type and case volume influence surgery selection and clinical outcome. Higher surgery rates are observed in facilities with better survival outcomes. Abstract : For cases with early‐stage non–small cell lung cancer, both facility type and case volume influence surgery selection and clinical outcome. Case volume demonstrates a relatively modest effect compared with facility type. The ranking of odds of performing surgery closely follows the ranking of survival outcome, which largely explains the difference in survival outcome noted among different facilities.